2018
DOI: 10.1371/journal.pone.0203784
|View full text |Cite
|
Sign up to set email alerts
|

Changes in HIV prevention programme outcomes among key populations in Kenya: Data from periodic surveys

Abstract: The Kenya National AIDS and STI Control Programme (NASCOP) conducted annual polling booth surveys (PBS) in 2014 and 2015 to measure outcomes from the national HIV prevention programme for key populations (KPs), comprising behavioural, biomedical and structural interventions. KPs included female sex workers (FSWs), men who have sex with men (MSM) and people who inject drugs (PWID). We compared survey results from the first and second rounds. Comparing the second to the first round, significantly more FSWs (93% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

5
4

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…A technical brief (Interagency Working Group on Key Populations 2014) demonstrated that young key populations are more vulnerable to HIV due to widespread discrimination, stigma and violence (Vitek et al 2014), and the particular vulnerabilities of youth (Godia et al 2014), power imbalances in relationships and, sometimes, alienation from family and friends (Mutumba and Harper 2015). The high level of stigma prevents their access and utilization of HIV prevention and treatment services (Musyoki et al 2018). In addition, these young people within key populations often have lower knowledge of HIV risks, or lower ability to mitigate those risks such as negotiating condom use (Dellar et al 2015), compared with their older, more experienced counterparts (Wanje et al 2017) Access to services is influenced by negative health providers attitudes (Godia et al 2014) with HIV service providers often poorly equipped to serve young key populations, while the staff of programs for young people may lack the appropriate sensitivity, skills and knowledge (Delany-Moretlwe et al 2015;Shabani et al 2018) Policy makers and health providers in our study cited the need to address legal provisions that limit the services that those under 18 years can get in the facilities as the law restricts what health providers can provide including HIV testing and counseling services without parental consent.…”
Section: Discussionmentioning
confidence: 99%
“…A technical brief (Interagency Working Group on Key Populations 2014) demonstrated that young key populations are more vulnerable to HIV due to widespread discrimination, stigma and violence (Vitek et al 2014), and the particular vulnerabilities of youth (Godia et al 2014), power imbalances in relationships and, sometimes, alienation from family and friends (Mutumba and Harper 2015). The high level of stigma prevents their access and utilization of HIV prevention and treatment services (Musyoki et al 2018). In addition, these young people within key populations often have lower knowledge of HIV risks, or lower ability to mitigate those risks such as negotiating condom use (Dellar et al 2015), compared with their older, more experienced counterparts (Wanje et al 2017) Access to services is influenced by negative health providers attitudes (Godia et al 2014) with HIV service providers often poorly equipped to serve young key populations, while the staff of programs for young people may lack the appropriate sensitivity, skills and knowledge (Delany-Moretlwe et al 2015;Shabani et al 2018) Policy makers and health providers in our study cited the need to address legal provisions that limit the services that those under 18 years can get in the facilities as the law restricts what health providers can provide including HIV testing and counseling services without parental consent.…”
Section: Discussionmentioning
confidence: 99%
“…Cohort effects could also be a plausible reason for the higher lifetime prevalence of police harassment among older YSW given the 2014 scale-up of police education to reduce police-mediated violence and harassment against sex workers in Kenya. (35) Another reason for the difference in police harassment by age may be the potential for increased visibility of older sex workers to law enforcement. Finally, the high and similar prevalence of recent physical or sexual violence, and of police harassment among those who ever experienced it, across age-groups may be due to ongoing or repeated experience of these vulnerabilities over the sexual life-course of YSW -as previously shown with female sex workers in general across SSA.…”
Section: Reproductive Health Vulnerabilities By Age (Table 4)mentioning
confidence: 99%
“…Previous trend showed new HIV infections in major cities of Nairobi and Mombasa increased by more than 50% (from a collective total of 4,707 in 2013 to 7,145 in 2015. This implies that the HIV prevalence ranges widely from one region to another, For instance Wajir had a prevalence of 0.1% in 2016 compared to the 25.4% reported in Homa Bay in the same period [11,12].…”
Section: Introductionmentioning
confidence: 99%